2015
DOI: 10.14202/vetworld.2015.718-722
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of growth performance in pre-weaning suckling Boer kids supplemented with creep feed containing alfalfa

Abstract: Aim:This study examined the effects of creep feed (CF) supplementation (with or without Alfalfa) on the pre-weaning growth performance of nursing goat kids.Materials and Methods:A total of forty eight (48), 7 days old, single born kids (live weight 4.4±0.09 kg) were divided into three treatment groups, each containing eight males and eight females. All three groups had access to their dams’ milk (DM). The kids from the first treatment group had free access to CF containing alfalfa (CFA) while those from the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“… Goetsch et al (2002) reported no increase in weight gain or kid weights when an 18% CP creep feed was consumed at 152 g/d on pasture from 6 to 19 wk of age. Creep feeding increased kid growth rates in Htoo et al (2015) with kids consuming 230 g/d of a 14% CP feed in a pen-based, intensive management system from 7 to 84 d of age. Differences in management systems likely explain differences among studies for kid responses to creep feed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Goetsch et al (2002) reported no increase in weight gain or kid weights when an 18% CP creep feed was consumed at 152 g/d on pasture from 6 to 19 wk of age. Creep feeding increased kid growth rates in Htoo et al (2015) with kids consuming 230 g/d of a 14% CP feed in a pen-based, intensive management system from 7 to 84 d of age. Differences in management systems likely explain differences among studies for kid responses to creep feed.…”
Section: Resultsmentioning
confidence: 99%
“…Effects on creep feeding on preweaning weight gain in lambs have been variable ( Glimp, 1971 ; Wilson et al, 1971 ; de Villiers et al, 2002 ; Brand and Brundyn, 2015 ). Two studies published on goats ( Goetsch et al, 2002 ; Htoo et al, 2015 ) have also produced mixed results. Despite limited data, numerous outreach publications exist guiding meat goat producers in creep feeding and there are various commercial creep feeds and creep feeders designed for meat goats available for producers to purchase.…”
Section: Introductionmentioning
confidence: 99%
“…The growing goat kids fed cricket creep feed had higher average daily gain (123 g/d) [ 12 ] compared to the BSF creep feed treatment (89 g/d). It is reported that kids with intensive management could increase growth rate with consumption of 230 g/d of creep feed containing 14% CP based alfalfa [ 18 ]. Other experiments reported that with the supplementation of 18% CP creep feed, the consumption is around 152 g/d and no difference in weight gain [ 19 ].…”
Section: Aplication Of Black Soldier Fly Larvae In Ruminant Rationsmentioning
confidence: 99%
“…Creep feed consists of crushed grains, and leaf meal of different fodder species can also be mixed with grains. Generally, kids of 3-4 weeks age, start nibbling, but they can be very selective, with preference shown for leguminous leaf meals, alfalfa in particular [30]. Leaf meals of Acacia, Sesbania, Leucaena and some species of Prosopis are also preferred.…”
Section: Management Of New Born Kidsmentioning
confidence: 99%